2019
DOI: 10.1186/s10194-019-0985-0
|View full text |Cite|
|
Sign up to set email alerts
|

Primary headaches during lifespan

Abstract: Primary headaches are one of the most prevalent neurological disorders and can occur during a wide range of lifespan. Primary headaches, especially migraine, are cyclic disorders with a complex sequence of symptoms within every headache attack. There is no systematic review of whether these symptoms changes during lifespan. Indeed, the clinical presentation of migraine shows an age-dependent change with a significantly shorter duration of the attacks and occurrence of different paroxysmal symptoms, such as vom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 170 publications
(198 reference statements)
1
64
1
5
Order By: Relevance
“…However, females usually outnumber male patients in migraine trials, including studies of the other neuromodulatory approaches [61][62][63] . On the one hand, this fact corresponds to the overall higher prevalence of migraine in women in epidemiological studies 4,64,65 . On the other hand, this ratio tends to be even more pronounced in treatment trials -an observation not extensively studied so far.…”
Section: Discussionmentioning
confidence: 96%
“…However, females usually outnumber male patients in migraine trials, including studies of the other neuromodulatory approaches [61][62][63] . On the one hand, this fact corresponds to the overall higher prevalence of migraine in women in epidemiological studies 4,64,65 . On the other hand, this ratio tends to be even more pronounced in treatment trials -an observation not extensively studied so far.…”
Section: Discussionmentioning
confidence: 96%
“…The male:female ratio was 4:3, but the ratio seems to be changing, with more women being diagnosed than men [ 8 ]. The lifetime prevalence in three European countries (Sweden, Germany, Italy) ranged from 0.15% to 0.28% [ 11 ]. Cluster headache presents with sudden onset of unilateral head pain, usually involving the eye and hemicranium, accompanied by parasympathetic autonomic manifestations such as tearing, nasal congestion, forehead sweating, miosis and ptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic migraines with low prevalence produce an extremely high disability [27]. The peak of prevalence of the most frequent primary headaches is in the very period that encompasses occupationally and reproductively active years [28][29][30][31][32]. In a Dutch study with 1781 employees who received a questionnaire, of the 1082 who responded (60.8%), the prevalence of headaches was 53.3%, with 39.8% of participants having at least one type of headache [7].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies demonstrated that headaches adversely affect various aspects of the sufferer's life [25][26][27][28][29][30]. Trying to understand how a headache influenced work efficiency in our subjects, we asked them how a headache affects their work by offering several answers and allowing them to specify some other effects of their headaches.…”
Section: Discussionmentioning
confidence: 99%